2012
DOI: 10.2135/cropsci2012.02.0118
|View full text |Cite
|
Sign up to set email alerts
|

Weeping Lovegrass Yield and Nutritive Value Provides an Alternative to Beef Cattle Feeding in Semiarid Environments of Argentina

Abstract: Weeping lovegrass[Eragrostis curvula (Schrad.) Nees] supports extensive beef cattle operations in arid and semiarid environments worldwide. This perennial grass is preferred in low production areas of Argentina because it has a high biomass production with minimal management requirements. Therefore, we evaluated yield and nutritional value of seven different cultivars and accessions of weeping lovegrass in a field experiment during two consecutive years (Two tetraploid cultivars (Tanganyika and Morpa), three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Higher protein content (80–160 g kg −1 ) in a given feed is usually desirable for maintenance, growth, production and normal feed intake and functioning of rumen microflora. Generally, the CP content for all treatments from this study was within the range reported for weeping lovegrass (63–175 g kg −1 ) . It was also above the minimum crude protein requirement of ruminants (70–80 g kg −1 )…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Higher protein content (80–160 g kg −1 ) in a given feed is usually desirable for maintenance, growth, production and normal feed intake and functioning of rumen microflora. Generally, the CP content for all treatments from this study was within the range reported for weeping lovegrass (63–175 g kg −1 ) . It was also above the minimum crude protein requirement of ruminants (70–80 g kg −1 )…”
Section: Discussionsupporting
confidence: 77%
“…Generally, the CP content for all treatments from this study was within the range reported for weeping lovegrass (63-175 g kg −1 ). 25,26 It was also above the minimum crude protein requirement of ruminants (70-80 g kg −1 ). 24 The year × sludge application treatment interaction for CP was primarily caused by CP magnitude differences among years.…”
Section: Crude Protein Contentmentioning
confidence: 92%